2008
DOI: 10.1063/1.2912486
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between luminescent properties and local coordination environment for erbium dopant in yttrium oxide nanotubes

Abstract: The local dopant coordination environment and its effect on the photoluminescent ͑PL͒ spectral features of erbium-doped yttrium oxide nanotubes ͑NTs͒ were probed by synchrotron-based x-ray diffraction ͑XRD͒, x-ray absorption near-edge spectroscopy ͑XANES͒, and extended x-ray absorption fine structure ͑EXAFS͒. XRD, XANES, and EXAFS data demonstrate that single phase solid solutions of Y ͑2−x͒ Er x O 3 were formed at 0 Յ x Ͻ 0.4 and 1.2Ͻ x Յ 2, and the valence state of Er ions in the Y 2 O 3 NTs is +3. The x-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…This distance is 8.5% shorter than the average Er−Er distance reported for the solid-state structure of Er 2 O 3 with 6 Er at 3.496 Å. 74 The contraction for the liquid electrolyte is correlated with the decrease in the number of Er nearest neighbors with respect to that for the solid oxide. The three shell fit to the I e(⊥) EXAFS for the liquid electrolyte is shown as dashed lines in Figure 5, and the metrical results are provided in Table 2 of the Supporting Information.…”
Section: ■ Experimental Methodsmentioning
confidence: 72%
See 1 more Smart Citation
“…This distance is 8.5% shorter than the average Er−Er distance reported for the solid-state structure of Er 2 O 3 with 6 Er at 3.496 Å. 74 The contraction for the liquid electrolyte is correlated with the decrease in the number of Er nearest neighbors with respect to that for the solid oxide. The three shell fit to the I e(⊥) EXAFS for the liquid electrolyte is shown as dashed lines in Figure 5, and the metrical results are provided in Table 2 of the Supporting Information.…”
Section: ■ Experimental Methodsmentioning
confidence: 72%
“…Precedent is provided by the observations made here and elsewhere 68 Figure 7 of the Supporting Information). 74,75 Although ligand-field effects are certainly at play for the liquid electrolyte system studied here, they are smaller than the spectral resolution of the beamline optics, suggesting an O CN greater than six and, therefore, cannot be resolved in the second differential of the XANES data. EXAFS.…”
Section: ■ Experimental Methodsmentioning
confidence: 97%
“…In addition, powder and synchrotron XRD analyses confirmed that these 5% Er 3+ :Y 2 O 3 NTs are of a cubic bixbyite Y 2 O 3 structure ͑space group: Ia3͒, 41 without observable impurities ͑data not shown here͒. 32,33…”
Section: Resultsmentioning
confidence: 90%
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] For example, we have recently reported detailed studies on syntheses and morphological and crystal structural characterization of one dimensional ͑1D͒ erbium-doped yttrium hydroxide ͓Er 3+ :Y͑OH͒ 3 ͔ NTs and erbiumdoped yttrium oxide ͑Er 3+ :Y 2 O 3 ͒ NTs and the effect of local Er 3+ dopant coordination environments on the photoluminescent spectral features of Er 3+ :Y 2 O 3 NTs. 32,33 Overall, the optical properties of individual nanosized luminescent emitters have received much attention, mainly on elemental, II-VI, and III-V semiconductors. [34][35][36][37][38] These low-dimensional systems show interesting fundamental properties and have exciting prospects in nanotechnologyenabled optical and electronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…It is also smaller than that of the Y 2 O 3 :Er 3+ thin film prepared by radical-enhanced atomic layer deposition. 19 28-30 It should be pointed out that if the Er 3+ is distributed irregularly in different crystallographic sites, it will randomize the Stark splitting, 31 resulting in a homogeneous spectral broadening. It is found that the fluorescence spectrum of the sample sintered at 700 C around 1535 nm is extremely sharp and well-resolved.…”
Section: Resultsmentioning
confidence: 99%